THE EFFECT OF WORD CLAP GAME IN LEARNING VOCABULARY - Andi Tenri Wulandari; Ratna Dewi; Awalia Azis (FKIP Unismuh Makassar, 2021)
This research aimed to know whether the use of Word Clap game gave effect or not for the students in learning vocabulary to the 7th grade at SMPN 1 Kajuara.The researcher used a Pre-Experimental Research with one group Pretest and Posttest design which consisted of eight meeting included the treatments. The data of the students’ vocabularies were taken from Pretest and Posttest. The population of the research was the seventh grade students of SMPN1 Kajuara consist of 8 classes, the total of number of sample were 20 students in class 7C and the sample was taken by using purposive sampling technique. The data was obtained by matching the words test. The research findings showed that the seventh Grade students of SMPN 1 Kajuara had poor score in Pretest. After treatment, their vocabulary mastery increased significantly. The students ‘mean score in word meaning as subject were 41.75 in Pretest and become 76.10 in Posttest. The result of hypothesis testing of this research was (Sig (2-tailed) was 0.000, because of Sig < α (0.000 < 0.05), it can be concluded that Pretest and Posttest has sig < α, and H1 was accepted and H0 was rejected. It means that it had been significance by using Word Clap Game for students ‘vocabulary mastery. The student’s development their vocabulary is 82%. It is supported by the value of t-test that is bigger than the value of t-table (36.422>2.093). It was concluded that the use of Word Clap Game was effective to improve the students ‘vocabularies.